A new target for the treatment of endometrium cancer by succinic acid - Iplik, Elif Sinem; Catmakas, Tolga; Cakmakoglu, Bedia (Cellular and Molecular Biology, 2018)
Endometrium cancer is the most common invasive gynecologic malignancy in developed countries. Succinic acid (CO2HCH2-CH2CO2H) is a type of dibasic acid that has uncolored crystal. Succinic acid is used in bakery products and aromatized products. It is naturally found in some vegetables. Succinic acid has no adverse effects because it is metabolized by body cells and has a role in the tricarboxylic acid cycle (TCA) as a cycle media component. The TCA cycle and its enzyme components have some crucial roles for basal cell metabolism. Any mistakes, concentration differences in product, or enzyme deficiencies are important within the cell this cycle. In this proposal project, we aimed to investigate the effect of succinic acid at different doses and at different times in an endometrial cancer cell line. The study was performed using methods that determine for apoptosis (for cytotoxicity, WST-1, for caspase enzyme activity, Caspase 3/BCA; apoptotic determination using flow cytometry; Annexin V; to understand mitochondrial membrane potential; JC-1). The results showed that 5 and 10 µM concentration of succinic acid resulted in apoptosis in endometrium cancer; no such effect was seen in the control cell line, which comprised healthy lung cells.  According to our results, it is thought that succinic acid would be effective for the treatment of endometrial cancer cell lines, thus providing new data for other areas of cancer research.